Periprostatic adipose tissue (PPAT) supernatant from obese mice releases anticontractile substances and increases human prostate epithelial cell proliferation: the role of nitric oxide and adenosine - Passos, Gabriela Reolon; de Oliveira, Mariana G.; Ghezzi, Ana Carolina; Mello, Glaucia C.; Levi D’Ancona, Carlos Arturo; Teixeira, Simone Aparecida; Muscará, Marcelo Nicolas; Grespan Bottoli, Carla Beatriz; Vilela de Melo, Lucilia; de Oliveira, Eliezer; Antunes, Edson; Mónica, Fabiola Zakia (Frontiers in Pharmacology, 2023)
Background: The prostate gland is surrounded by periprostatic adipose tissue (PPAT) that can release mediators that interfere in prostate function. In this study, we examined the effect of periprostatic adipose tissue supernatant obtained from obese mice on prostate reactivity in vitro and on the viability of human prostatic epithelial cell lines. Methods: Male C57BL/6 mice were fed a standard or high-fat diet after which PPAT was isolated, incubated in Krebs-Henseleit solution for 30 min (without prostate) or 60 min (with prostate), and the supernatant was then collected and screened for biological activity. Total nitrate and nitrite (NOx−) and adenosine were quantified, and the supernatant was then collected and screened for biological activity. NOx− and adenosine were quantified. Concentration-response curves to phenylephrine (PE) were obtained in prostatic tissue from lean and obese mice incubated with or without periprostatic adipose tissue. In some experiments, periprostatic adipose tissue was co-incubated with inhibitors of the nitric oxide (NO)-cyclic guanosine monophosphate pathway (L-NAME, 1400W, ODQ), adenylate cyclase (SQ22536) or with adenosine A2A (ZM241385), and A2B (MRS1754) receptor antagonists. PNT1-A (normal) and BPH-1 (hyperplasic) human epithelial cells were cultured and incubated with supernatant from periprostatic adipose tissue for 24, 48, or 72 h in the absence or presence of these inhibitors/antagonists, after which cell viability and proliferation were assessed. Results: The levels of NOx− and adenosine were significantly higher in the periprostatic adipose tissue supernatant (30 min, without prostate) when compared to the vehicle. A trend toward an increase in the levels of NOX was observed after 60 min. PPAT supernatant from obese mice significantly reduced the PE-induced contractions only in prostate from obese mice. The co-incubation of periprostatic adipose tissue with L-NAME, 1400W, ODQ, or ZM241385 attenuated the anticontractile activity of the periprostatic adipose tissue supernatant. Incubation with the supernatant of periprostatic adipose tissue from obese mice significantly increased the viability of PNT1-A cells and attenuated expression of the apoptosis marker protein caspase-3 when compared to cells incubated with periprostatic adipose tissue from lean mice. Hyperplastic cells (BPH-1) incubated with periprostatic adipose tissue from obese mice showed greater proliferation after 24 h, 48 h, and 72 h compared to cells incubated with culture medium alone. BPH-1 cell proliferation in the presence of PPAT supernatant was attenuated by NO-signaling pathway inhibitors and by adenosine receptor antagonists after 72 h. Conclusion: NO and adenosine are involved in the anticontractile and pro-proliferative activities of periprostatic adipose tissue supernatant from obese mice. More studies are needed to determine whether the blockade of NO and/or adenosine derived from periprostatic adipose tissue can improve prostate function.